Instructional design communication through AI-assisted storytelling: a hybrid model grounded in educational psychology - Yifan Pan; Muhammad Zammad Aslam (Frontiers in Psychology, 2026)
Introduction Artificial intelligence (AI)-assisted storytelling is increasingly transforming educational communication and instructional design, particularly in isolated and remote learning environments. However, challenges related to collaboration, meaningful interaction, technological accessibility, and ethical use remain. Drawing on educational psychology, this study investigates how AI-assisted storytelling communication strategies can support cognitive engagement, motivation, creativity, collaboration, and stakeholder engagement in AI-supported educational communication systems. It also examines how digital communication technologies are restructuring instructional design communication and how storytelling can be integrated with AI-mediated communication to address emerging educational challenges. Methods This qualitative study employed narrative interviews with 16 digital instructional designers and AI developers selected through purposive sampling. Data were collected through semi-structured interviews, case studies, and content analysis of relevant instructional design and educational communication practices. The collected data were analyzed using thematic analysis to identify recurring patterns related to instructional design communication, educational communication, storytelling practices, digital collaboration, and AI-mediated communication. Results The findings indicate that although digital technologies have facilitated communication and collaboration among educational teams, particularly in remote environments, they may also reduce opportunities for deep interpersonal interaction. Technologies such as Artificial Intelligence (AI), WeChat, and VooV Meeting have enhanced communication dynamics but have introduced challenges, including the absence of non-verbal cues and unequal access to technology. Emerging technologies such as AI, Virtual Reality (VR), and Augmented Reality (AR) are reshaping instructional design by creating more engaging learning experiences; however, concerns regarding ethical use, accessibility, equity, and fairness remain. Storytelling emerged as an effective strategy for strengthening educators' engagement, improving understanding, fostering creativity, and promoting stakeholder collaboration. Discussion/Conclusion The findings suggest that AI-assisted storytelling can provide a meaningful communication strategy for addressing the collaborative and interactional limitations of digitally mediated educational environments. The study therefore proposes the "Hybrid Storytelling-Digital Communication (HSDC) Model", which integrates storytelling with AI-supported digital communication tools to promote meaningful interaction, creativity, collaboration, and stakeholder engagement while addressing ethical, accessibility, and equity concerns.